1992
DOI: 10.1002/cm.970210303
|View full text |Cite
|
Sign up to set email alerts
|

Reactivation of newt lung cilia: Evidence for a possible temperature‐ and MgATP‐induced activation mechanism

Abstract: Optimal conditions have been developed for the isolation and reactivation of highly coupled, demembranated ciliary axonemes from newt lungs [Hard, Cypher, and Schabtach, 1988, Cell Motil. Cytoskeleton 10:271-284]. In the present study, the motility of these cilia was further characterized by examining the effects of nucleotides, divalent cations, and temperature on beat frequency. When exposed to a reactivating solution containing Mg2+ and ATP, nearly 100% of the axonemes were motile and beat at frequencies of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…
Demembranated axonemes isolated from newt lung ciliated cells show a complex beat frequency response to varying [MgATP] and temperature [Hard and Cypher, 1992, Cell Motil. Cytoskeleton 21:187-1981.
…”
mentioning
confidence: 99%
“…
Demembranated axonemes isolated from newt lung ciliated cells show a complex beat frequency response to varying [MgATP] and temperature [Hard and Cypher, 1992, Cell Motil. Cytoskeleton 21:187-1981.
…”
mentioning
confidence: 99%
“…Beat frequencies of ciliated cells vary considerably according to the method of isolation, culture, etc. Since beat frequency constitutes a “health meter” built into ciliated cells, it is important for subsequent experimentation that maximum frequencies approach 20 Hz or greater, based on data in vertebrate systems 4 . Cilia beating at low, unphysiologic frequencies may be unresponsive to agents that activate signal transduction pathways, thereby giving erroneous results.…”
Section: Discussionmentioning
confidence: 99%
“…Erythrocyte lysis buffer consisted of 0.15 M NH 4 CL, 10 mM KHCO 3 , 0.1 mM Na 2 EDTA in deionized H 2 O and was prepared fresh before each use. Cell viability was determined using trypan blue dye exclusion, and cells were plated at seeding densities of no less than 2 × 10 4 /cm 2 on type I collagen (Cellogen Discs, Costa Mesa, CA) in media consisting of DMEM/F12‐containing antibiotics and 5 g/mL insulin, 1 μM hydrocortisone, 10 ng/mL L‐isoproterenol, 0.5 ng/mL EGF, and 5% FBS and 1 × 10 −8 retinoic acid.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Purified, demembranated axoneme models reactivate with exogenous MgATP and beat at frequencies comparable to those recorded for intact cells. Hard and Cypher [1992] have shown that the beat frequency kinetics of these highly coupled axonemes is biphasic in response to MgATP concentration and temperature. Recently, have demonstrated that the outer dynein arms can be selectively removed from isolated, demembranated newt lung ciliary axonemes by high salt (0.375 M) extraction in a manner similar to sea urchin or trout sperm flagellar axonemes.…”
Section: Introductionmentioning
confidence: 99%